The Financial Health Analysis and Income Diversification Case Study on Indonesia Corruption Watch (ICW): Financial Health Analysis and Income Diversification Case Study on Indonesia Corruption Watch (ICW) - Patridhina, Gineung (Jurnal Manajemen dan Bisnis Madani, 2024)
NGOs are agents of change that were formed with the aim of meeting social development needs that have not been able to be carried out or fulfilled by the government as state administrator. To maintain their existence, NGOs are required to maintain healthy financial conditions and diversified funding to ensure the survival of the organization so that it can provide a sustainable impact for its beneficiaries. Therefore, measuring NGO financial performance is very important. The aim of this research is to determine the financial performance and funding diversification of the NGO Indonesia Corruption Watch (ICW). The method used in this research is qualitative descriptive using financial ratio analysis and funding diversification on secondary data obtained from the website https://antikorup.org, in the form of financial reports for 2017-2021. The financial ratios calculated to measure ICW's financial performance use the ratio measurement method developed by Ritchie and Kolodinsky (2003), as well as funding diversification which will be measured using the Hirschman Herfindahl Index (HHI). The research results show that the financial health of ICW is in the good category with diversified income, it is known that the level of dependency on main donors is small. This has a positive impact on the sustainability of ICW to be able to continue to advocate for strengthening the people's bargaining position to control the state and participate in decisions to realize democratic governance, free from corruption, with economic, social and gender justice.